Evaluasi Penggunaan Antibiotik Profilaksis pada Pasien Bedah Sesar di RS X Kabupaten Cianjur Periode Oktober-Desember Tahun 2022: Evaluation of Prophylaxis Antibiotics Uses in C-Section Patients at X Hospital Cianjur Regency from Periode of October-December 2022 - Dikna Nur Apriliana; Fifi Agustari; Julia Totong (UIMA Press, 2023)
Cesarean section is an artificial birth through an open abdominal incision (laparotomy) and an incision in the uterus (hysterotomy). Included in the type of clean contaminated surgery that requires the use of prophylactic antibiotics to prevent infection of the operating area. The purpose of this study was to evaluate the appropriate use of prophylactic antibiotics in cesarean section patients at X Hospital, Cianjur Regency. This research was conducted using a non-experimental method, accompanied by a descriptive observational analysis design based on retrospective data from the medical records of cesarean section patients at X Hospital, Cianjur Regency. Based on the results of a study of 70 samples, it was found that the prevalence of C-sections at X Hospital Cianjur Regency for the periods of October-December 2022 period was mostly carried out in the age range of 17-30% (44.29%). The prophylactic antibiotics used were cefotaxime (58.57%), cefazolin (31.43%), and ceftriaxone (10%). The selection of the type of antibiotic and the method of administration was 100% correct according to the reference used. However, during dosing, 48 samples (68.57%) received the correct dose, and 22 samples (31.43%) did not receive the correct dosage regimen according to the reference used. Timing of prophylactic antibiotic administration for C-sections should be completed within 60 minutes before the initial incision, preferably at the time of induction of anesthesia. Because giving prophylactic antibiotics 30 to 59 minutes before the initial incision can reduce the risk of infection of the operating area.